Chitosan affects total nutrient digestion and ruminal fermentation in Nellore steers - Araújo, A. P C; Venturelli, B. C.; Santos, M. C B; Gardinal, R.; Cônsolo, N. R B; Calomeni, G. D.; Freitas, J. E.; Barletta, R. V.; Gandra, J. R.; Paiva, P. G. [UNESP]; Rennó, F. P. (Elsevier, 2015)
This study aimed to investigate the effects of chitosan on dry matter intake (DMI), nutrient digestibility, ruminal fermentation, and blood metabolites in Nellore steers. Eight ruminally cannulated Nellore steers (540±28.5kg of BW) were used in a replicated 4×4 Latin square design, with 21-d of experimental periods. The animals were randomly assigned to the following treatments: control (without chitosan addition; Q0), Q50, Q100 and Q150, by dosing 50, 100 and 150mg/kg BW chitosan, respectively, through the cannula. Although there was no difference on DMI, chitosan addition increased dry matter, neutral detergent fiber, and crude protein apparent total-tract digestibility (P<0.05). Ruminal pH was not affected, whereas NH3N concentration was quadratically affected with chitosan addition (P=0.01). There were no differences in total volatile fatty acids concentration among treatments. Chitosan had a quadratic effect on propionate and butyrate, whereas acetate molar proportions decreased linearly (P<0.05). Acetate:propionate ratio decreased with chitosan addition (P<0.05). Plasma glucose concentration was higher with chitosan addition (P<0.05); however, total protein, urea, aspartate aminotransferase, and gamma-glutamyl transferase were not affected by chitosan. Addition of chitosan altered ruminal fermentation, improved nutrient digestibility, and did not appear to damage animal health.
Keywords: Beef cattle; Blood parameters; Chitosan; Digestibility; Intake; Ruminal fermentation